Revitalizing Samiʻna wa Athoʻna: Strengthening Reasoned Obedience for Merdeka Belajar Character Education: Merevitalisasi Samiʻna wa Athoʻna: Menguatkan Ketaatan Beralasan untuk Pendidikan Karakter Merdeka Belajar - Rachmatullah Rusli (Journal of Educational Research and Learning Analytics, 2025)
This study examines the integration of the Islamic pedagogical principle Sami’na wa Atho’na (“we hear and we obey”) with Indonesia’s Merdeka Belajar Curriculum to strengthen character education under the Profil Pelajar Pancasila framework. Through a qualitative descriptive approach, the research comprises three phases: a theological-literature review of Qur’anic and classical sources to map the spectrum of Sami’na wa Atho’na beyond passive obedience; ethnographic fieldwork in pesantren, madrasah, and Islamic schools to identify pedagogical manifestations and distortions; and a triangulation synthesis validated by experts via focus group discussions. Findings reconceptualize Sami’na wa Atho’na as “enlightened obedience,” a meta-competency foundational to disciplined autonomy, ethical commitment, and internalized integrity. This framework bridges the apparent dichotomy between obedience and learner freedom, providing practical guidelines for policymakers, teacher training institutes, and PAI teachers. The study affirms that reasoned obedience underpins responsible independence, ensuring that freedom in learning becomes purposeful, ethical, and sustainable.